Aboveground litter production and bioelement potential return in an evergreen oak (Quercus rotundifolia) woodland near Salamanca (Spain) - Martin, A; Gallardo, J F; Santa Regina, I (Ann. For. Sci., 1996)
Total aboveground production of trees has been determined in a Quercus rotundifolia evergreen oak woodland developed over a chromic Luvisol. The woodland is located close to the city of Salamanca (central-western Spain). Litter fall occurs throughout the year, with a maximum from April to June owing to leaf fall. Mean litter production is 1.9 Mg ha-1 year-1, although variations from year to year are observed, mostly due to water stress in summer. The mean area of influence of litter fall of each tree is about 4 m outside the crown shadow and the leaf percentage (55%) over the total aboveground litter production shows that the system is mature. Tree inflorescences are found to have the highest concentration in bioelements, although the latter are mostly returned through the leaves (with the exception of K).
Keywords: biogeochemical cycles; evergreen oak; litter fall; potential return of bioelements; Quercus rotundifolia Lam

Dynamics of bioelements during leaf decomposition in three forest ecosystems of semiarid climate in the Duero Basin - Hernández, M I; Santa Regina, I; Gallardo, J F (Arid Soil Research and Rehabilitation, 1995)
The dynamics of bioelements lost during leaf litter decomposition were experimentally determined in three forest ecosystems located in a semiarid zone of the Duero Basin, Province of Zamora, Spain, during 2 years. The three ecosystems were a climax Quercus rotundifolia (evergreen oak) woodland, a paraclimax Pinus pinea (stone pine) forest, and a disclimax P. pinaster (maritime pine) forest. The total content of bioelements found in the litter was low in relation to other forest ecosystems: 27, 14, and 8 kg N ha?1 in Q. pyrenaica, P. pinea, and P. pinaster, respectively; 17, 10, and 9 kg Ca ha?1, respectively; about 2 kg P ha?1, 4 kg K ha?1, and 5 kg Mg ha?1 in the three forests. The Q. rotundifolia woodland potentially returns a greater amount of N and Ca than both Pinus forests. An in situ litter bag method was used for the determination of dynamics of the decomposing leaves. A progressive loss of C, P, and Mg in the decomposing oak leaves and pine needles, and a sharp loss of K were observed; by comparison, a tendency to maintain N and Ca was seen. Pinus pinaster forest had the lowest annual N and P return.
doi: 10.1080/15324989509385911
Keywords: biogeochemical cycles; litter decomposition; pine forests; Quercus rotundifolia; semiarid forests

Dinámica de la descomposición de la hojarasca forestal en bosques de la cuenca del duero (provincia de zamora): Modelización de la pérdida de peso - Hernandez, I M; Santa Regina, I; Gallardo, J E (Arid Soil Research and Rehabilitation, 1992)
Resumen Se ha estudiado la pérdida de peso en el proceso de descomposición de hojarasca en tres ecosistemas forestales de la zona semiárida Cuenca del Duero: un encinar climácico de Quercus rotundifolia Lam., un pinar paraclimácico de Pinus pinea L., y un pinar disclimácico de P. pinaster Ait. No se encuentran diferencias significativas entre la dinámica de descomposición de las hojas en cada ecosistema, salvo cuando las hojas de encina se colocan en otros ecosistemas. La pérdida de peso se ajusta a una curva exponencial negativa. En todos los casos, durante los cuatro primeros meses de experimentación, el peso original se reduce en un 30%. Ello parece indicar que es la climatología quien dirige fundamentalmente, a corto plazo, el proceso de descomposición. En condiciones naturales, los índices de descomposición (K j y K o) siguen la secuencia: encina > pino piñonero > pino marítimo, tanto en hojas como en hojarasca total.
doi: 10.1080/15324989209381328
Keywords: forest ecosystems; semiarid area; wight loss modeling